2011
DOI: 10.1038/modpathol.2010.178
|View full text |Cite
|
Sign up to set email alerts
|

International Society of Urological Pathology (ISUP) Consensus Conference on Handling and Staging of Radical Prostatectomy Specimens. Working group 1: specimen handling

Abstract: The 2009 International Society of Urological Pathology Consensus Conference in Boston made recommendations regarding the standardization of pathology reporting of radical prostatectomy specimens. Issues relating to the handling and processing of radical prostatectomy specimens were coordinated by working group 1. Most uropathologists followed similar procedures for fixation of radical prostatectomy specimens, with 51% of respondents transporting tissue in formalin. There was also consensus that the prostate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
162
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 244 publications
(166 citation statements)
references
References 57 publications
0
162
1
3
Order By: Relevance
“…Although it is generally accepted that up to 2 hours of warm ischemia (time without fixation) does not alter protein, DNA or RNA conformation or preservation of microscopic, and IHC features (Burns et al 2009), Samaratunga et al (2011) have reported that even before resection has been completed, intraoperative manipulations can alter gene transcription levels during radical prostatectomies. Spruessel et al (2004) used microarray analysis, quantitative real-time polymerase chain reaction, and surface enhanced laser desorption ionization time of flight to investigate changes in gene and protein expression in normal and cancerous colon tissue at various stages of ischemia.…”
Section: Specimen Collection and Transportationmentioning
confidence: 99%
“…Although it is generally accepted that up to 2 hours of warm ischemia (time without fixation) does not alter protein, DNA or RNA conformation or preservation of microscopic, and IHC features (Burns et al 2009), Samaratunga et al (2011) have reported that even before resection has been completed, intraoperative manipulations can alter gene transcription levels during radical prostatectomies. Spruessel et al (2004) used microarray analysis, quantitative real-time polymerase chain reaction, and surface enhanced laser desorption ionization time of flight to investigate changes in gene and protein expression in normal and cancerous colon tissue at various stages of ischemia.…”
Section: Specimen Collection and Transportationmentioning
confidence: 99%
“…The results of the individual working group reports related to specimen handling, T2 substaging, extraprostatic extension and seminal vesicle and lymph node involvement are reported separately. [13][14][15][16] Many recommendations of this consensus conference have already been incorporated into international guidelines, including the recent College of American Pathologists protocol and checklist for reporting adenocarcinoma of the prostate, and the structured reporting protocol for prostatic carcinoma from the Royal College of Pathologists of Australasia. 17,18 Definition and criteria for positive surgical margins A positive surgical margin can be defined as tumor that extends to the surface of the prostate wherein the surgeon has cut across the tissue plane.…”
Section: International Society Of Urological Pathology (Isup) Consensmentioning
confidence: 99%
“…Kad tumor makroskopski nije vidljiv kod poštednog načina, pregledaju se u potpunosti stražnji dijelovi žlijezde i po jedan uzorak sa svake strane iz srednjeg i prednjeg dijela režnja. U usporedbi s uzorčenjem cijele žlijezde, ovom se metodom u 100 % slučajeva detektiraju pozitivni rubovi, a u 96 % širenje u tkiva izvan prostate 11,12 . Slika 4 prikazuje rezove kroz regije prostate.…”
Section: Prostatektomijaunclassified